Language Disorders in Siblings with Cadel: A Psycholinguistic Study - Faarisah, Shabrina; Azzahra, Aulia; Putra, Dona Aji Karunia (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study aims to describe the factors causing and forms of lisp in 5 and 6 year old male siblings with the initials ABR and YSF. This study was conducted using a descriptive qualitative method. The data in this study were in the form of speech produced by ABR and YSF as research subjects who are lisp sufferers. The data collection tech3niques applied in this study were interviews, and listen and note (SLC). The results of the study showed that there was alisp sufferers that caused difficulties and errors in pronouncing several phonemes in their use in a word, both at the beginning, in the middle, and at the end of the word. In this case, YSF experienced a lisp in the pronunciation of the phonemes /L/, /R/, /X/ and /Z/, while ABR experienced a lisp in the pronunciation of consonant phonemes in the form of pronunciation of phonemes /G/, /K/, /L/, /Q/, /R/, /X/, and /Z/, In addition, based on the results of interviews conducted with the subject's parents, it was concluded that the lisp suffered by ABR and YSF was caused by physiological factors and environmental factors. This study provides an important contribution to the study of early childhood psycholinguistics, especially in understanding the factors that influence lisp . In addition, this study can be a basis for the development of more specific and contextually based speech therapy, which can help children overcome pronunciation disorders from an early age.